Veratrum nigrum L. (Melanthiaceae) на Лівобережжі України - Жигаленко, О.А.; Лобань, Л.О. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2008)
Описан ареал Veratrumnigrum L. в Украине. Указаны новые местонахождения вида на Левобережье Украины и условия его произрастания. The range of Veratrum nigrum L. in Ukraine is described. New localities of the species in areas to the east of the Dnieper are reported. Habitats of the species are characterized.